Substorm Influences on Plasma Pressure and Current Densities Inside the Geosynchronous Orbit. Issue 3 (21st March 2023) - Fu, Haobo; Yue, Chao; Zong, Q.‐G.; Zhou, XuZhi; Yu, Yiqun; Li, Yuxuan; Liu, Jianjun; Hu, Zejun; Yang, Huigen; Reeves, Geoffrey D.; Spence, Harlan E.; Gerrard, Andrew J.; et al.
Abstract: Plasma in the inner magnetosphere is affected by various processes, such as substorms. In this study, we have statistically investigated the ring current properties based on the observations of Van Allen Probes from 2012 to 2019 to examine the substorm effects on the plasma pressure and current system in the inner magnetosphere. The results show that the plasma pressure increases significantly, leading to a ∼3 nT/hr geomagnetic depression during intense substorms. The contribution of <100 keV H + ions to the plasma pressure increases during substorms, which is more significant at lower L ‐shells. Opposite to the H + ions, the proportion of >10 keV O + ions contributing to the plasma pressure increases as substorm intensity increases. In addition, the rise of plasma pressure is mainly distributed from dusk to midnight, resulting in the enhancement of asymmetric ring current and the region II field‐aligned currents connecting to the ionosphere. Our results provide a comprehensive view of the variation of plasma pressure and current system in the inner magnetosphere during quiet periods and intense substorms. Key Points: The pressure increase caused by intense substorms can lead to 3 nT/hr magnetic field depression The pressure contribution of both <100 keV H + and >10 keV O + increase during intense substorms The ring current densities from dusk to midnight and region II FACs increase dramatically during intense substorms